Does income inequality have a heterogeneous effect on carbon emissions between developed and developing countries? Evidence from simultaneous quantile regression - Che, Cheng; Li, Suhui; Yin, Qi; Li, Qing; Geng, Xin; Zheng, Huixian (Frontiers in Environmental Science, 2023)
Two major challenges in the sustainable development process are income inequality and carbon emissions. However, there is not a certain conclusion to the links of income inequality and carbon emissions. In addition, for developed and developing countries, the impact might vary. Based on an international perspective, the present study examines the correlation between income inequality and carbon emissions utilizing panel data from 65 countries (32 developed and 33 developing) spanning from 1990 to 2019. The simultaneous quantile regression results show that the impact of income inequality on carbon emissions varies slightly between countries with various income levels. The positive impact of income inequality on carbon emissions is significant for both developed and developing countries, indicating unequal income distribution can worsen environmental quality, but the impact is more significant for developed countries. Therefore, it is integral for the global world to take measures to alleviate income gap to achieve sustainable development goals. In particular, more than income growth, developed countries also need to focus on income equity to reach green development.